New consensus, new Keynesianism, and the economics of the third way - Philip Arestis; Malcolm Sawyer (Levy Economics Institute of Bard College, 2002)
In this paper we seek first to set out the economic analysis that underpins the ideas of what has been termed the third way. The explicit mention of the third way is much diminished since the early days of the Blair government in the UK and the Schroeder government in Germany. We argue that the ideas associated with the third way continue to influence these governments and, more broadly, other governments and the European Union, and that these ideas are firmly embedded in New Keynesian economics. Our paper then focuses on some particular aspects of New Keynesian economics and its emphasis on the role of monetary policy and the downgrading of fiscal policy. There has emerged a so-called new consensus on macroeconomic policy (specifically, monetary policy), which we regard as an outgrowth of New Keynesian economics. We review this new consensus and argue that the empirical evidence on the operation of monetary policy reveals that such a policy is rather impotent. Insofar as it does have an effect, it operates to influence the level of investment, which in turn affects the future level and distribution of productive capacity. Thus, contrary to the prevailing view, monetary policy is not an effective way to control inflation, but it can have effects on the real side of the economy. The lack of attention to fiscal policy and the overemphasis on monetary policy leaves the European Union and its member countries without the means to tackle any serious recession or upsurge of inflation.
Keywords: 330